2006
DOI: 10.1892/0891-6640(2006)20[694:eiahwc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography in a Horse with Cor Pulmonale from Recurrent Airway Obstruction

Abstract: A 440-kg, 25-year-old Quarter horse mare presented to the University of Minnesota Veterinary Medical Center for assessment of recurrent airway obstruction. She had exhibited a seasonal (summer and fall) cough for the past 5 years. The latest cough began 4 months before presentation and did not respond to treatment with dexamethasone or prednisone. The mare was housed on pasture and fed alfalfa hay and sweet feed. Vaccinations and deworming were current. The mare was in good body condition and had a normal rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 8 publications
(11 reference statements)
0
22
0
4
Order By: Relevance
“…A few cases reported hypoxaemia from severe pulmonary diseases in horses as low as 79 mmHg (Sage et al . ), 71.4 mmHg (Schwarzwald et al . ) and 61 mmHg (Hanka et al .…”
Section: Discussionmentioning
confidence: 99%
“…A few cases reported hypoxaemia from severe pulmonary diseases in horses as low as 79 mmHg (Sage et al . ), 71.4 mmHg (Schwarzwald et al . ) and 61 mmHg (Hanka et al .…”
Section: Discussionmentioning
confidence: 99%
“…In früheren Studien konnte mittels konventioneller Echokardiographie nur bei hochgradig COB-kranken Pferden eine Hypertrophie des rechten Herzens oder eine Dilatation des rechten Ventrikels im Sinne eines Cor pulmonale nachgewiesen werden (Sage et al 2006, Johansson et al 2007). Demgegenüber zeigten invasive Herzkatheter-Druckmessungen Unterschiede zwischen COB und Kontrollpferden (Dixon 1978, Dixon et al 1982, Seiffert 1997.…”
Section: Introductionunclassified
“…Horses, in contrast, rarely develop pulmonary vascular anatomical changes, even in the face of long-standing pulmonary hypertension and hypoxia (Dixon et al 1982). The most common chronic pulmonary disease of horses in Northern Europe is recurrent airway obstruction (heaves) and although affected horses almost universally develop pulmonary hypertension (Dixon 1978), cor pulmonale is seldom observed (Sage et al 2006). The lungs of horses suffering from recurrent airway obstruction (RAO) do not develop the vascular anatomical changes seen in other species (Dixon et al 1982).…”
mentioning
confidence: 99%
“…Although the basis for the difference between horses and other species is not clear, it does appear that the ability of the equine pulmonary vascular system to respond to hypoxia with functional, rather than anatomical, changes may be a mechanism that protects against development of cor pulmonale. However, right ventricular hypertrophy does develop in a small proportion of RAO cases secondary to hypoxia-driven pulmonary hypertension (Dixon et al 1982;Sage et al 2006) and clinicians should be vigilant for this minority of RAO-affected horses with cor pulmonale. It has been suggested that it is the intermittent nature of RAO that prevents cor pulmonale and that it might be expected to occur more frequently in response to chronic, persistent pulmonary disease (Sage et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation